Immune System and Its Relation to Depression - Wati Evilia; Anak Ayu Sri Wahyuni; Luh Alit Aryani (Jurnal Psikiatri Surabaya, 2021)
It has been shown that the immune system and mental status are interrelated. Psychoneuroimmunology is a field that studies these two relationships, one of the most studied is the relationship between the immune system and depression. Psychological stress can substantially increase inflammatory activity and increase risk for various health problems. Socioal-environmental conditions trigger biological responses that may lead to an increase in the proinflammatory phenotype which is hypothesized to be a key phenomenon driving the pathophysiology and relapse of depression, as well as the overlap of depression with several somatic conditions such as rheumatoid arthritis, chronic pain, cardiovascular disease, and neurodegeneration. The immune system and depression have a bidirectional link that influences each other. Exposure to chronic stressful situations can cause a maladaptive response by the immune system, which will be involved in the pathophysiology of depression.